Fluid-Driven Instabilities in Granular Media: From Viscous Fingering and Dissolution Wormholes to Desiccation Cracks and Ice Lenses - Liu, Qi; Santamarina, J. Carlos (Frontiers in Mechanical Engineering, 2022)
Single and multi-phase fluids fill the pore space in sediments; phases may include gases (air, CH4, CO2 H2, NH3), liquids (aqueous solutions or organic compounds), and even ice and hydrates. Fluids can experience instabilities within the pore space or trigger instabilities in the granular skeleton. Then, we divide fluid-driven instabilities in granular media into two categories. Fluid instabilities at constant fabric take place within the pore space without affecting the granular skeleton; these can result from hysteresis in contact angle and interfacial tension -aggravated in particle-laden flow-, fluid compressibility, changes in pore geometry along the flow direction and contrasting viscosity among immiscible fluids. More intricate fluid instabilities with fabric changes take place when fluids affect the granular skeleton, thus the evolving local effective stress field. We consider several cases: (1) open mode discontinuities driven by drag forces, i.e., hydraulic fracture; (2) grain-displacive invasion of immiscible fluids, such as desiccation cracks, ice and hydrate lenses, gas and oil driven openings, and capillary collapse; (3) hydro-chemo-mechanically coupled instabilities triggered by mineral dissolution during the injection of reactive fluids, from wormholes to shear band formation; and (4) instabilities associated to particle transport (backward piping erosion), thermal changes (thermo-hydraulic fractures), and changes in electrical interparticle interaction (osmotic-hydraulic fractures and contractive openings). In all cases, we seek to identify the pore and particle-scale positive feedback mechanisms that amplify initial perturbations, and to identify the governing dimensionless ratios that define the stable and unstable domains.